Implementation of improvement cycle in health records of mobile emergency prehospital care - Maria do Socorro Telma Batista Araújo Timóteo; Rodrigo Assis Neves Dantas; Ilanne Caroline Santos Costa; Tâmara Taynah Medeiros da Silva; Kauanny Vitoria Gurgel dos Santos; Eloysa dos Santos Oliveira; Daniele Vieira Dantas (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to evaluate the effect of the implementation of a quality improvement cycle in the completion of occurrence forms of a Mobile Emergency Service. Methods: this is a time series, quantitative, quasi-experimental study without control group, with three quality assessments in which was used an improvement cycle for adequacy of health records in Mobile Emergency Service Patos. Results: in 100% of the seven criteria, there was improvement between evaluations. Noncompliance with criteria reduced from 95 cases in the first evaluation to eight cases in the third evaluation. Conclusions: the representation of joint results between the three evaluations highlighted progressive improvement in the compliance with each criterion.